Optimization of Flavonoid Compounds from Avocado Seeds Using Ethanol Solvent through Response Surface Methodology (RSM) - Laurentcya, Treyna Dara; Fergilang, Jibraltar; Sari, Ni Ketut; Nurherdiana, Silvana Dwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This research aimed to optimize the extraction of flavonoid compounds from avocado seeds (Persea Americana Mill.) using ethanol as a solvent through Response Surface Methodology (RSM). Avocado seeds are known to contain bioactive compounds, including flavonoids, which exhibit antioxidant properties. Extraction was performed via maceration using 96% ethanol, with varying extraction times (1–5 days) and seed powder-to-solvent ratios (10–50% w/v). The results demonstrated that prolonged extraction time and higher solvent ratios significantly increased flavonoid yield, peaking at 6.5090% (5 days, 50% w/v). RSM optimization (25 data points) identified optimal conditions at 4.99414 days and a 39.6367% w/v ratio, yielding 3.65815% flavonoids. GC-MS analysis detected degraded flavonoid derivatives (e.g., avocadenofuran), attributed to high-temperature processing. The study confirms ethanol-based maceration as an effective method for flavonoid extraction, with time and solvent ratio being critical factors. These findings support potential applications in the food and pharmaceutical industries for the development of antioxidant products. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action